Fasies dan lingkungan pengendapan Formasi Bobong berumur Jura sebagai pembawa lapisan batubara di Taliabu, Kepulauan Sanana-Sula, Maluku Utara - Kusnama Kusnama (Geological Agency, 2008)
http://dx.doi.org/10.17014/ijog.vol3no3.20085The Bobong Formation is a coarse clastic sedimentary rock succession. In the lower part, it consists of breccia and conglomerate facies, then followed by quartz sandstone with intercalations of claystone facies. Upwards, the rock succession is gradually changed to become alternating shale, claystone and mudstone. In the upper section the rock unit is well exposed in the western and northern parts of the Taliabu Island. The formation is Jurassic in age and it was deposited within a fluvial-transition to shallow marine environ- ment. The coal bed found within quartz sandstone and shale and claystone-mudstone facies ocupies the upper part succession of the Bobong Formation. The coal in the Taliabu Island has two seams having a thickness of 30 - 40 cm and 100 - 120 cm, respectively. The geochemical analysis result indicates that the calorific value ranges from 6,186 to 7,350 cal/g, the sulphur content is from 3% to 4.65% , fixed carbon ranges from 45.69 to 53,96%, and ash content from 7.86 - 16.37%. On the basis of those parameter, the coal within the Bobong Formation is categorized as subbituminous to high volatile bituminous rank.